Analysis of Sexual Violence Elimination Bill Against Victim Protection Reviewed from Progressive Legal Aspects - Satria, Wahyu Putra; Kurniaty, Yulia; Basri, B; Krisnan, Jhony (Prosiding University Research Colloquium, 2022)
This study aims to describe a progressive legal view of existence and analyze what forms of protection are provided for victims of sexual violence in the the BILL of elimination of sexual violence. This research uses a normative juridical approach (statute approach) and a conceptual approach. Based on the results and discussion, we will discuss progressive legal views on existence and analyze what forms of protection for victims of sexual violence are in the Bill on the Elimination of Sexual Violence. In the opinion of the researcher, the enforcement of existing laws and regulations in Indonesia is still lacking in taking sides with victims of sexual violence in terms of handling and recovery. However, the researcher agrees if the Draft Law on the the BILL of elimination of sexual violence is passed, because it is with the existence of the the BILL of elimination of sexual violence into the The Sexual Violence Elimination Act, it is hoped that this is a legal provision that specifically accommodates Indonesian laws and regulations that have been in existence so far. previously did not regulate in detail and comprehensively in tackling cases of sexual violence.